Building a unique online corporate identity - Abdullah, Zulhamri; Md Nordin, Shahrina; Abdul Aziz, Yuhanis (Emerald Group Publishing, 2013)
Purpose: The purpose of this paper is to examine the current state of mission and vision statements on corporate websites of Malaysian and Singaporean corporations based on Aaker's brand personality dimensions and analyze how the dimensions are effectively used to develop a unique corporate identity. Design/methodology/approach: Content analysis is employed to examine similarities and differences for 300 Malaysian and 214 Singaporean consumer corporations based on Aaker's big five brand personality framework. Findings: Generally most companies tend to publish and communicate their mission and vision statements visibly to general stakeholders. First, both Malaysian and Singaporean companies have weak brand personality dimensions which reflect the projection of corporate identity of companies. Second, there is a significant difference in the brand personality dimensions between Malaysian and Singaporean consumer corporations. Finally, evidence showed that most Malaysian and Singaporean companies rather failed to position themselves in the marketplace using brand personality dimensions in their vision and mission statements. This may affect their overall organizational direction in building a unique corporate identity and gaining competitive advantages within the context of a global business environment. Practical implications: The study acknowledges the increase in communicating the mission and vision statements on the corporate websites of Malaysian and Singaporean corporations. However, there is a need for corporations in Malaysia and Singapore to orchestrate their core competence in order to develop a unique corporate identity in a global business environment. Originality/value: The study contributes to the corporate identity literature in providing an insight into how corporations communicate the desired brand personality through their websites for the critical inquiry of the dominant coalition and main stakeholders.